Pedro Calderón de la Barca. Las cadenas del Demonio. Eds., José Elías Gutiérrez Meza y Henrry A. Ibáñez Mogrovejo. Madrid/ Frankfurt: Iberoamericana/Vervuert, 2024. 196 pp. - Montauban, Jannine (2025)
No presenta resumen.